Development of Interactive E-Module Based on Canva as a Digital Learning Media in the Construction of Dressmaking - Syarifah Suryana; St. Aisyah; Rosmiaty; Israwati Hamsar (Jurnal MediaTIK, 2025)
Effective instruction in dressmaking requires digital learning media capable of presenting procedural information with clarity, precision, and interactivity. This study aims to develop and evaluate an interactive Canva-based e-module for the Dressmaking course in vocational higher education. A Research and Development (R&D) design employing the 4D model (Define, Design, Develop, Disseminate) was implemented with 40 undergraduate students. Product validity was assessed by material and media experts, while practicality and effectiveness were examined through student response questionnaires and pre–post learning achievement tests. Data were analyzed using descriptive statistics, N-Gain, paired sample t-test, and effect size. The results indicate a validity score of 91.25%, a practicality score of 90.0%, and an improvement in learning outcomes with an N-Gain of 0.68, along with a significant difference between pre- and post-test scores (t = 8.24; p < 0.001) and a large effect size (Cohen’s d = 1.30). These findings demonstrate that the Canva-based e-module effectively enhances students’ conceptual and procedural mastery in dressmaking. The study underscores the module’s potential for integration into multimedia-based vocational instruction and hybrid or LMS-supported learning environments.